BUDAYA GURU SEKOLAH DASAR DALAM PEMBELAJARAN ( Studi Situs SD Negeri 1 Getasrejo Kecamatan Grobogan) - NARTO, NARTO (2011)
The objectives of the study are: 1) describe the culture of a public elementary school teachers 1 Getasrejo Grobogan district administration in the preparation of learning; 2) describe the culture of a public elementary school teachers 1 Getasrejo Grobogan District in the implementation of learning; 3) describe the culture of a public elementary school teachers 1 Getasrejo Grobogan district in the evaluation and follow-up learning. This type of research is a qualitative study using ethnographic approaches. Research conducted at the School District Elementary School 1 Getasrejo Grobogan Grobogan district . The informants in this study were headmasters, teachers , and students from elementary School 1 Getasrejo Grobogan District . Data collection techniques using in-depth interviews, observation, documentation Based on research results , we conclude that : 1) Culture of Primary School Teachers' School 1 Getasrejo District Administration Grobogan In the preparation of Learning. In the planning phase teachers Getasrej o Elementary School 1, always make the administration of preparation of the semester program, syllabus, Learning Implementation Plan (RPP), materials, worksheets, visual aids before implementing learning; 2) Culture of Primary School Teachers' School 1 Getasrejo District Grobogan In the Implementation of Learning. At the implementation stage of learning, the teacher opened the lesson by praying together and giving greetings in advance, which continued with varying activity . Submission of goals is an important part and is always done. Submission of material carried by the right method, the teachers act as facilitators who guide, nurture, and motivate students for learning, teachers treat students with both appropriate level of ability, in the process of teaching and learning, teachers use active learning model . Learn multi-way interaction can be seen from the implementation of learning. For high grade (4, 5, 6) the intensity of interaction of multi-direction better than the early grades (grades 1, 2, 3). Closed by providing reinforcement learning, strengthening the material , evaluating, cooling, singing, and giving homework assignments, 3) Cultural School 1 Elementary School Teacher District Getasrejo Grobogan In Evaluation And Follow-Up Study. At this sta ge of evaluation and follow-up, teachers implement and use terulis tests, oral tests, deed, performance , and observation and by carrying out remedial and enrichment programs.